2017
DOI: 10.1155/2017/6724631
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Monocular Deprivation Enhances Physiological Pupillary Oscillations

Abstract: Short-term monocular deprivation alters visual perception in adult humans, increasing the dominance of the deprived eye, for example, as measured with binocular rivalry. This form of plasticity may depend upon the inhibition/excitation balance in the visual cortex. Recent work suggests that cortical excitability is reliably tracked by dilations and constrictions of the pupils of the eyes. Here, we ask whether monocular deprivation produces a systematic change of pupil behavior, as measured at rest, that is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…In line with previous studies (26,27,29,30,43), short-term monocular contrast deprivation induced a 30% increase of phase duration for the deprived eye (POST to PRE-deprivation ratio: 1.30 ± 0.31) and a 15% decrease of phase duration for the non-deprived eye (ratio: 0.86 ± 0.31), producing a significant time × eye interaction (Fig. 3A, repeated measure ANOVA on the mean phase durations for each participant, interaction: F(1,17) = 21.40085, p = 0.00024).…”
Section: Monocular Deprivation Boosts V1 Responses To the Deprived Eysupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies (26,27,29,30,43), short-term monocular contrast deprivation induced a 30% increase of phase duration for the deprived eye (POST to PRE-deprivation ratio: 1.30 ± 0.31) and a 15% decrease of phase duration for the non-deprived eye (ratio: 0.86 ± 0.31), producing a significant time × eye interaction (Fig. 3A, repeated measure ANOVA on the mean phase durations for each participant, interaction: F(1,17) = 21.40085, p = 0.00024).…”
Section: Monocular Deprivation Boosts V1 Responses To the Deprived Eysupporting
confidence: 92%
“…For example, selective deprivation of one cardinal orientation over few hours leads to paradoxically enhanced sensitivity to the deprived orientation (25). Similarly, short-term monocular deprivation leads to a transient boost of the deprived eye responses (26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…The improvement in visual acuity of about 2 lines lasted for up to one year, indicating long-term neuroplastic changes . Binda & Lunghi (2017) more recently tackled another biomarker of neuroplasticity in adult humans by demonstrating that monocular deprivation affects spontaneous low frequency oscillations of the pupil diameter at rest, a phenomenon called hippus (Diamond, 2001). The authors measured pupillary oscillations before and after monocular occlusion, following the same paradigm as Lunghi et al (2011), and found that hippus amplitude increased after visual deprivation and that participants with more pronounced pupillary fluctuations also showed stronger ocular dominance changes in binocular rivalry dynamics.…”
Section: Cortical Plasticity In Sighted Adults Revealed By Shortterm mentioning
confidence: 99%
“…Finally, in light of the recent results by Binda & Lunghi (2017) showing both increased pupillary hippus at rest and enhanced eye-dominance of the deprived eye during binocular rivalry after monocular deprivation, the role of the neurotransmitter norepinephrine (NE) in mediating homeostatic plasticity should be further investigated in adult humans. This neurotransmitter may indeed constitute the common source of visual cortical excitability underlying these phenomena, given its known role in regulating both pupil diameter modulation (Joshi et al, 2016) and visual cortical plasticity (Kasamatsu et al, 1979(Kasamatsu et al, , 1981.…”
Section: Neurochemical Changes Following Short-term Visual Deprivationmentioning
confidence: 99%
See 1 more Smart Citation